2012
DOI: 10.1002/cphc.201100810
|View full text |Cite
|
Sign up to set email alerts
|

NMR Investigation of Imidazolium‐Based Ionic Liquids and Their Aqueous Mixtures

Abstract: (1)H and (13)C NMR spectroscopy is employed to investigate the interaction of water with two imidazolium-based ionic liquids (ILs), 1-hexyl-3-methylimidazolium bromide ([C(6)mim]Br) and 1-octyl-3-methylimidazolium bromide ([C(8)mim]Br), at IL concentrations well above the critical aggregation concentration (CAC). The results are compared with those of the neat samples. To this aim, a detailed analysis of the changes in the (1)H chemical shifts, (13)C relaxation parameters, and 2D ROESY data due to the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 52 publications
7
39
0
Order By: Relevance
“…The peak assignments were validated according to other NMR studies in neat ILs. [40][41][42] As MWCNTs are added to [BMIM] [HSO 4 ] (top 3 spectra on Figure 5b) there is a broadening of all the peaks. The broadening is likely due to inhomogeneous local magnetic fields caused by the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The peak assignments were validated according to other NMR studies in neat ILs. [40][41][42] As MWCNTs are added to [BMIM] [HSO 4 ] (top 3 spectra on Figure 5b) there is a broadening of all the peaks. The broadening is likely due to inhomogeneous local magnetic fields caused by the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Communications alkyl chain exhibit a pronounced upfield shift with increasing incubation time (Figure 2 c) compared to the individual IL, which indicates an interaction with water during co-assembly, [14] as evidenced by the FTIR spectra and all-atom molecular dynamics (AAMD) simulations ( Figures S5,S6). Therefore, such a LLPS-mediated co-assembly process governed by multiple dynamic noncovalent interactions differs from the CaCO 3 crystallization dominated by strong ionic interactions.…”
Section: Angewandte Chemiementioning
confidence: 87%
“…Some of the studies mentioned in section 3.1 on pure liquids also contained data on solutions or mixtures. Thus, Hayamizu and co-workers 180 studied lithium salt solutions in RTILs, using among others 7 Li T 1 measurements, Lingscheid et al 183 studied ionic liquids dissolved in dichloroethane and dimethylsulfoxide, while Marincola et al 184 studied mixtures of RTILs with water. In addition to these works, Yasaka et al 203 reported MD simulations of RTIL solutions of water and benzene, aiming at improved interpretation of earlier experimental data from the same group.…”
Section: Electrolyte Solutionsmentioning
confidence: 97%